Zaragoza city From victory to collapse - Shukairat, Hussein Raja (Journal of Humanities & Social Sciences, 2018)
This study seeks to examine the causes of the fall of the city of Zaragoza in Andalusia and giving a brief history of this city since opened by Muslims to fall but the Franks. Mtnaolina also study the importance of this city through various Islamic basis either in the reign of the Emirate or Caliphate era or even in the era of the taifas. Relying on the totality of the studies on the history of Andalusia, although these studies relevant exhaustive studies had served a year and most of it did not deal with the history of the Islamic cities of Andalusia are particularly hoping that this will be the first study other studies deal with circumstantial account topics Rise and fall of historical citie
Keywords: Zaragoza; the era of the caliphate; the era of the emirate; the Kingdom of Aragon